Rethinking Dickens in the light of Osip Mandelstam’s case (ENTHYMEMA, 2016)
The Russian presence of Dickens can generally be reduced to several types: first, he is a “teacher” admired at the national level, the creator of the “Christmas narrative canon”; second, a mythological figure, his texts being the source of parables and anecdotes; finally, his name has turned into a common thing, an object of everyday life, a symbol in the representative list of European writers. Mandelstams' poem “Dombey and son” is a pattern of Russian Dickensian.